2014
DOI: 10.1117/1.jbo.20.5.051002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mixtures of compounds produced in chlorpromazine aqueous solutions by ultraviolet laser irradiation: their applications in antimicrobial assays

Abstract: The study reports an investigation of the photoproducts obtained by exposure of chlorpromazine hydrochloride in ultrapure water (concentration 2 mg/mL) to a 266-nm laser beam obtained by fourth harmonic generation from a Nd:YAG laser (6-ns full time width at half maximum, 10-Hz pulse repetition rate). The photoproducts were analyzed by steady-state UV-Vis absorption, laser-induced fluorescence, Fourier transform infrared spectroscopy, and liquid chromatography-tandem time-of-flight mass spectroscopy. Two figur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…The CPZ samples at 2 mg/mL in ultrapure water irradiated 1, 5, 15, 30, 60, 120,180 and 240 min were analysed using LC-TOF/MS. Results showed seven CPZ generated photoproducts: promazine (PZ), P1, P2, 2-hydroxypromazinesulfoxide (2-HO-PZ-SO), chlorpromazine sulfoxide (CPZ-SO), promazine sulfoxide (PZ-SO) and 2-hidroxipromazine (2-HO-PZ) [ 13 ]. We mention that the photoproducts MSO and SPZ may also be used as antipsychotics.…”
Section: Introductionmentioning
confidence: 99%
“…The CPZ samples at 2 mg/mL in ultrapure water irradiated 1, 5, 15, 30, 60, 120,180 and 240 min were analysed using LC-TOF/MS. Results showed seven CPZ generated photoproducts: promazine (PZ), P1, P2, 2-hydroxypromazinesulfoxide (2-HO-PZ-SO), chlorpromazine sulfoxide (CPZ-SO), promazine sulfoxide (PZ-SO) and 2-hidroxipromazine (2-HO-PZ) [ 13 ]. We mention that the photoproducts MSO and SPZ may also be used as antipsychotics.…”
Section: Introductionmentioning
confidence: 99%
“…A 2 mL volume of TZ solutions were irradiated 1, 5, 15, 30, 60, 120, 180, or 240 min with 266 nm pulsed beam emitted by Nd:YAG laser (10 Hz, 6 ns FWHM) according to the irradiation protocol detailed in Alexandru et al (2014) 46 .…”
Section: Methodsmentioning
confidence: 99%
“…The set-up utilized to study the stability of the irradiated phenothiazines solutions is shown in Fig.1a where a variant of a more general system described in [3,4] is drawn.…”
Section: Set-upmentioning
confidence: 99%
“…Recent reports have shown that phenothiazines solutions as parent compounds, when exposed to ultraviolet (UV) laser radiation generate photoproducts that have different molecular structures and properties with respect to them [1][2][3][4]. More recent studies show that solutions of phenothiazines in water once exposed to laser radiation have modified wetting properties with respect to fabrics [5].…”
Section: Introductionmentioning
confidence: 96%